2019
DOI: 10.3926/ic.1353
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the CEO in listed family businesses

Abstract: Purpose: Our objective is to analyze the influence that the type of CEO has on the management of listed family businesses in Spain, distinguishing between whether the CEO is a family member or not. The study mainly focuses on his/her influence on levels of profitability. Design/methodology: During de period from, 2012 to 2016, with data coming from Iberian Balance Sheet Analysis System (SABI) database. To analyze the effects of the CEOs on family businesses, we carried out two kinds of analyses. First, a univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…These results confirmed that there are activities where it is easier for companies to obtain higher levels of profitability than in others. This result has also been reported in previous studies [45,79].…”
Section: Regression Modelsupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirmed that there are activities where it is easier for companies to obtain higher levels of profitability than in others. This result has also been reported in previous studies [45,79].…”
Section: Regression Modelsupporting
confidence: 93%
“…The results obtained demonstrate that the characteristics of the CEO, both his origin (family or external) or his level of studies, do not exert a statistically significant influence on the economic profitability of any group of family business. Previous works, such as that of Sánchez et al [45], already observed the absence of a significant influence that is derived from the origin of the CEO, indicating that the external CEO generates both positive and negative effects on profitability, which mutually counteract each other. If the absence of statistical significance on the part of the educational level is more pronounced, then this training is traditionally associated with (1) a greater capacity to process information and make quick decisions [80], (2) the ability to face scenarios of uncertainty [81], or (3) a greater adaptability to change [82].…”
Section: Regression Modelmentioning
confidence: 90%
See 1 more Smart Citation